Media dan Bahasa: Analisis Framing Entman terhadap Prabowo–Gibran dalam The Straits Times - Adinda Afifah Damayanti; Dadang Rahmat Hidayat; Siti Karlinah (Balai Bahasa Provinsi Bali, 2025)
This study aims to analyze how international media, specifically The Straits Times frames Prabowo Subianto and Gibran Rakabuming Raka candidacy in the 2024 elections in Indonesia using Robert Entman’s framing theory and the Systemic Functional Linguistics (SFL) approach by Halliday. Employing a qualitative descriptive method with textual analysis, the study identifies four key framing elements: the defined problem focuses on potential declines in electability due to political controversy; the diagnosed cause points to the Constitutional Court’s revised age requirement; moral judgment appears in the criticism of dynastic politics; and the implied solution emphasizes the need for transparency in political decisions. Meanwhile, the SFL approach reveals that the media’s language choices and sentence structures are not neutral, but instead shape specific representations that can influence public opinion. The use of material processes like “paved the way” and references such as “Jokowi’s brother-in-law” illustrates how language subtly yet effectively builds a particular political narrative. These findings affirm that media not only deliver information but also construct reader perspectives through strategic linguistic choices. AbstrakPenelitian ini bertujuan untuk mengkaji bagaimana The Straits Times membentuk narasi mengenai isu pencalonan Prabowo Subianto dan Gibran Rakabuming Raka pada Pemilu tahun 2024 di Indonesia melalui pendekatan framing Robert M. Entman, yang dipadukan dengan analisis linguistik dari Systemic Functional Linguistics (SFL) milik Halliday. Adapun penelitian ini menggunakan metode deskriptif kualitatif dengan teknik analisis teks. Hasil studi menunjukkan bahwa media tersebut menggunakan keempat elemen framing Entman: mendefinisikan masalah berupa penurunan elektabilitas Prabowo, mengaitkan penyebab dengan keputusan Mahkamah Konstitusi, menampilkan penilaian moral terhadap dugaan politik dinasti, serta menyiratkan solusi berupa perlunya transparansi. Selain itu, analisis SFL mengungkapkan bahwa pilihan leksikal dan struktur kalimat yang digunakan tidak bersifat netral. Ungkapan seperti “paved the way” dan penyebutan hubungan kekeluargaan dalam frasa “Jokowi’s brother-in-law” merupakan bentuk representasi makna yang secara halus mengarahkan opini pembaca. Temuan ini menegaskan bahwa media tidak hanya menyajikan informasi, melainkan juga secara strategis membingkai isu politik melalui penggunaan bahasa.